Evaluation of Anti-Corruption Values in Students: A Review from Character and Economic Perspectives - Santoso, Ridwan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jambi, 2025)
This study aims to evaluate the anti-corruption character of senior high school students through the perspective of character education and economics. The massive corruption phenomenon in Indonesia underlines the urgency of forming individuals with integrity from an early age. Although many prevention efforts have been carried out, comprehensive evaluation of the effectiveness of anti-corruption education in schools is still limited. This study focuses on two main pillars: how character education (including the values ​​of honesty, responsibility, and justice) and understanding of economic concepts (such as the impact of corruption on the economy and the importance of efficient resource allocation) shape students' anti-corruption attitudes and behaviors. The research method that will be used is quantitative descriptive with a survey approach. The research population is high school students in the Jambi region. The selection of the quantitative descriptive method is considered the most appropriate because it allows systematic data collection from a large number of respondents to describe the characteristics of the phenomenon being studied. Data will be collected through a structured questionnaire that measures the level of students' understanding of anti-corruption values, their attitudes toward acts of corruption, and their perceptions of the economic impact of corruption. This questionnaire will use a Likert scale to measure the level of respondent agreement with the statements given. The collected data will be analyzed using descriptive statistics to describe the profile of students' anti-corruption character based on character and economic perspectives. The results of the study are expected to provide a clear picture of the level of anti-corruption character of high school students and strategic recommendations for the development of a more effective anti-corruption education curriculum in the future.